2016
DOI: 10.1111/ncmr.12072
|View full text |Cite
|
Sign up to set email alerts
|

How Superior–Subordinate Relationship Quality and Conflict Management Styles Influence an Employee's Use of Upward Dissent Tactics

Abstract: This study examined employees’ use of upward dissent tactics to express disagreement with organizational policies or practices to their supervisors. Employees (N = 242) from three organizations completed a survey instrument in which they reported the types of upward dissent tactics and types of conflict management styles they used with their supervisors as well as their perceptions of the quality of those relationships. The integrating conflict management style was positively correlated with the prosocial diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 57 publications
1
10
1
1
Order By: Relevance
“…The fundamental importance lies in how conflict manages to consider the value of the relationship (49). Similarly, Redmond, Jameson, & Binder (2016) found that there was no significant relation between accommodating conflict management styles and relation quality with supervisors (50). This study results are inconsistent with those of Shojaee, et al, (2012) who found a significant relationship between conflict management styles used by leaders and the quality of vertical dyad linkage (51).…”
Section: Discussioncontrasting
confidence: 57%
“…The fundamental importance lies in how conflict manages to consider the value of the relationship (49). Similarly, Redmond, Jameson, & Binder (2016) found that there was no significant relation between accommodating conflict management styles and relation quality with supervisors (50). This study results are inconsistent with those of Shojaee, et al, (2012) who found a significant relationship between conflict management styles used by leaders and the quality of vertical dyad linkage (51).…”
Section: Discussioncontrasting
confidence: 57%
“…In several cases, employees demonstrate passive resistance to show their disagreement with managers’ decisions. These findings are consistent with research about passive dissent strategies resulting from unresolved or poorly managed conflict (Kassing, ; Redmond, Katz Jameson, & Binder, ). Overall, the findings about conflict strategies are consistent with PNG cultural values observed in conflict management (Barker, ; Burke et al., ; Young, ), as well as individual situational appraisals (Ting‐Toomey & Oetzel, ).…”
Section: Discussionsupporting
confidence: 89%
“…Building relationships and improving communication between supervisor and subordinate could be important preventatives that increase opportunities to resolve conflicts before anger expressions occur or minimize the negative outcomes that might follow. Recent studies examining the superior–subordinate relationship quality, conflict management style, and subordinate upward dissent tactics confirm that favorable relationships will facilitate upward dissent—in all its forms (Redmond et al., ). In addition, high‐quality superior–subordinate relationships were related to managers using a more integrative conflict management style, which is characterized as being open to learning from and understanding the others’ perspective and attempting to reach a consensual decision regarding disagreements.…”
Section: Discussionmentioning
confidence: 99%
“…For supervisors, anger from subordinates is a form of “employee voice” (Geddes & Callister, ) or “upward dissent” (Kassing, , ; Redmond, Jameson, & Binder, ) and could be perceived as an opportunity to learn real attitudes about the work situation; however, it could also be seen as inappropriate and out of line. The qualitative commentary included a relatively balanced view of seven positive and six negative outcomes.…”
Section: Methodsmentioning
confidence: 99%